2020
DOI: 10.3389/fphar.2020.01283
|View full text |Cite
|
Sign up to set email alerts
|

Interplay Between Angiotensin II Type 1 Receptor and Thrombin Receptor Revealed by Bioluminescence Resonance Energy Transfer Assay

Abstract: The key hormone of the renin-angiotensin system (RAS), angiotensin II (AngII), and thrombin are known to play major roles in the vascular system and its related disorders. Previous studies reported connections between AngII and thrombin in both physiological and pathophysiological models. However, the molecular mechanisms controlling such interplay at the level of their receptors belonging to the family of G protein-coupled receptors (GPCRs) are not fully understood. In this study, we investigated the function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 54 publications
(93 reference statements)
7
14
1
Order By: Relevance
“…Such trans‐activation required to a certain extent the activate conformation of PAR1 since it was partially blocked by PAR1 antagonist. More interestingly, we also found that the dual activation of AT1R and PAR1 led to synergistic effects regarding AT1R‐Gαq coupling and AT1R‐β‐arrestin association that were drastically inhibited by both AT1R and PAR1 selective antagonists [4]. This suggests a positive allosteric interaction between the two protomers both required to be active within the AT1R‐PAR1 heterodimer.…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…Such trans‐activation required to a certain extent the activate conformation of PAR1 since it was partially blocked by PAR1 antagonist. More interestingly, we also found that the dual activation of AT1R and PAR1 led to synergistic effects regarding AT1R‐Gαq coupling and AT1R‐β‐arrestin association that were drastically inhibited by both AT1R and PAR1 selective antagonists [4]. This suggests a positive allosteric interaction between the two protomers both required to be active within the AT1R‐PAR1 heterodimer.…”
mentioning
confidence: 89%
“…The major advances in the field of GPCR heterodimerization were possible thank to the development and application of various techniques such as the bioluminescence and fluorescence resonance energy transfer (BRET and FRET) and their derived assays allowing the study of GPCR pharmacology and signaling from multiple angles and prospects [3]. In this context, we recently reported an interesting functional interplay between the angiotensin II (AngII) type 1 receptor (AT1R) and the thrombin or protease‐activated receptor 1 (PAR1) in the human embryonic kidney (HEK293) cells using BRET technology [4]. This may be the molecular basis of the previous in vitro and in vivo studies reporting the interaction between the renin‐angiotensin system (RAS) and the protease thrombin in the vascular and renal systems [5–9].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Receptor-HIT has most commonly been used to investigate the pharmacology of receptor heteromers composed of two different GPCRs (termed GPCR-HIT) [10,12,[17][18][19][20][21][22][23][24]. GPCRs are the largest family of membrane receptors and are also the largest family of drug targets, with over 30% of currently approved drugs acting via GPCRs [25][26][27].…”
Section: Gpcr-gpcr Receptor-hitmentioning
confidence: 99%